Harnessing the potential of bulk segregant analysis sequencing and its related approaches in crop breeding - Majeed, Aasim; Johar, Prerna; Raina, Aamir; Salgotra, R. K.; Feng, Xianzhong; Bhat, Javaid Akhter (Frontiers in Genetics, 2022)
Most plant traits are governed by polygenes including both major and minor genes. Linkage mapping and positional cloning have contributed greatly to mapping genomic loci controlling important traits in crop species. However, they are low-throughput, time-consuming, and have low resolution, due to which their efficiency in crop breeding is reduced. In this regard, the bulk segregant analysis-sequencing (BSA-seq) and its related approaches, viz. quantitative trait locus (QTL)-seq, bulk segregant RNA-Seq (BSR)-seq, and MutMap have emerged as efficient methods to identify the genomic loci/QTLs controlling specific traits at high resolution, accuracy, reduced time span, and in a high-throughput manner. These approaches combine BSA with next-generation sequencing (NGS) and enable rapid identification of genetic loci for qualitative and quantitative assessment. Many previous studies have shown successful identification of the genetic loci for different plant traits using BSA-seq and its related approaches as discussed in the text with details. However, the efficiency and accuracy of the BSA-seq depend upon factors like sequencing depth and coverage, which enhance sequencing cost. Recently, the rapid reduction in the cost of NGS together with the expected cost-reduction of third-generation sequencing in the future will further increase the accuracy and commercial applicability of these approaches in crop improvement programs. This review article provides an overview of the BSA-seq and its related approaches in crop breeding together with their merits and challenges in trait mapping.